Bobble-Head Doll and Dandy-Walker Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A female infant with macrocephaly (head circumference >95th%), hydrocephalus, and Dandy-Walker syndrome, who developed horizontal head movements of the 'no-no' type at 1 year of age, is reported from Federal University of Minas Gerais, and other centers in Brazil.